Interstitial microbial communities of coastal sediments are dominated by Nanoarchaeota - Brick, Simone; Niggemann, Jutta; Reckhardt, Anja; Könneke, Martin; Engelen, Bert (Frontiers in Microbiology, 2025)
Microbial communities in subsurface coastal sediments are highly diverse and play an important role in nutrient cycling. While the major fraction of microorganisms in sandy sediments lives as epipsammon (attached to sand grains), only a small fraction thrives in the interstitial porewaters. So far, little is known about the composition of these free-living microbial communities. In the subsurface of the sandy beach, investigated in this study, we compared the archaeal and bacterial community structures within sediments and corresponding porewaters applying 16S rRNA gene sequencing. We found that the free-living prokaryotes only had a proportion of about 0.2–2.3% of the bulk communities, depending on the pore space. The interstitial microbial communities showed a small overlap with the attached fraction of 4–7% ASVs, and comprised a unique composition of 75–81% ASVs found exclusively in the porewaters. They were more diverse than the respective sediment-attached fraction and showed a much higher archaea-to-bacteria ratio. The archaea were mainly affiliated to Nanoarchaeota of the DPANN superphylum, with a relative abundance up to 50% of the interstitial communities. The bacterial fraction included several species related to the Candidate Phyla Radiation (CPR). Both prokaryotic lineages are known to have small cell sizes, comprising not-yet cultured species with unidentified metabolic functions. Our findings were supported by the investigation of an adjacent tidal flat, showing a similar trend. Thus, our results indicate the presence of distinct interstitial microbial communities in the subsurface of coastal sediments. This natural enrichment of not-yet cultured Nanoarchaeota and members of the CPR provides the opportunity for targeted metagenomic analyses or even isolating members of these groups for further metabolic characterization.